Sermon Collections of Johannes Eck in Transylvanian Libraries - COTOI, Paula (Studia Universitatis Babeș-Bolyai Historia, 2017)
Several libraries from Transylvania hold in their historical collections works written by an important figure of the early modern Catholicism, Johannes Eck (1486-1543). The present paper looks at the volumes of this author, printed in the first half of the sixteenth century, paying special attention to sermon collections, prevalent among the books found in Transylvania. Their number is rather small, but the analysis of ownerships marks allows formulating some observations. Thus, the bibliographic component of the study, which identifies the preserved volumes, some of which have not been cataloged so far, is accompanied by a historical approach that questions the context of their reception. With a few exceptions, in which the the clues about ownership and the use of books are either missing or very late, Eck's works seem to have been circulated both during the dissemination of the ideas of the Reformation and after the adoption of the new denominations. Rezumat: Colecții de predici ale lui Johannes Eck în bibliotecile din Transilvania. Câteva biblioteci din Transilvania păstrează în cuprinsul colecțiilor lor istorice lucrări ale unui important reprezentant al catolicismului epocii moderne timpurii, Johannes Eck (1486-1543). Lucrarea de față are în vedere volumele acestui autor, tipărite în prima jumătate a secolului al XVI-lea, acordând o atenție specială colecțiilor de predici, predominante în rândul cărților regăsite în Transilvania. Numărul acestora este destul de redus, dar analiza însemnărilor de proprietate permite formularea câtorva observații. Astfel, componenta bibliografică a studiului, prin care sunt identificate volumele păstrate, între care unele nu au fost catalogate până în prezent, este însoțită de o abordare istorică, ce chestionează contextul receptării lor. Cu câteva excepții, în care indiciile referitoare la proprietari și la utilizarea cărților fie lipsesc, fie sunt foarte târzii, lucrările lui Eck par a fi circulat atât în perioada răspândirii ideilor Reformei, cât și ulterior adoptării noilor confesiuni. Cuvinte-cheie: colecții de predici, Reformă, Johannes Eck, Mediascher Predigtbuch, misiune franciscană.